Analisis Kinerja Simpang APILL dengan Metode PKJI 2023 (Studi Kasus: Simpang Majapahit Kota Semarang) (Indonesian Journal of Civil Engineering Study, 2025)
The queue length at signalized intersections (APILL) significantly affects traffic congestion and overall traffic efficiency. This study analyzes the queue length at the Majapahit Intersection in Semarang through field measurements and the application of the 2023 Indonesian Highway Capacity Manual (IHCM/PKJI 2023) to identify approaches exceeding threshold values and validate the results against applicable standards. The findings indicate that queue lengths range from 71.72 m to 187.72 m, with the longest queue observed on the Gajah Raya Road approach (Degree of Saturation, DS = 1.15), surpassing the acceptable limit of 0.85. In contrast, the Brigjen Sudiarto Road and Majapahit Road approaches remain within safe operational thresholds. Validation results highlight the need for increased capacity and improved traffic management to reduce queue lengths. To enhance intersection performance, the study recommends improvements in road geometry, signal phase adjustments, and the implementation of more effective traffic management strategies aimed at minimizing queuing, reducing delays, and improving traffic flow.
Keywords: Degree of Saturation; Intersection Performance; Queue Length; Signalized Intersection